EXPLORING GENERATION Z EMPLOYEES' PERCEPTIONS OF KPI-BASED PERFORMANCE APPRAISAL SYSTEMS: A QUALITATIVE STUDY - Alis Andi Cahyono (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The increasing presence of Generation Z in the workforce has encouraged organizations to redesign performance management systems that align with the characteristics and expectations of younger employees. Among various performance management approaches, Key Performance Indicator (KPI)-based performance appraisal systems have been widely implemented to enhance organizational effectiveness through measurable performance evaluation. However, limited qualitative research has explored how Generation Z employees perceive these systems and how such perceptions influence their motivation and organizational commitment. This study aims to explore Generation Z employees' perceptions of KPI-based performance appraisal systems and to understand their implications for work motivation, individual job performance, and organizational commitment. A qualitative phenomenological approach was employed to capture employees' lived experiences and subjective interpretations regarding KPI implementation. Data were collected through semi-structured interviews and analyzed using thematic analysis. The findings indicate that transparency, fairness, and continuous feedback are essential factors shaping positive employee perceptions of KPI-based performance appraisal systems. Furthermore, employees perceive KPI systems as mechanisms that clarify organizational expectations, encourage self-development, and strengthen motivation when implemented in a supportive organizational environment. The study also reveals that developmental communication and coaching play significant roles in increasing employees' commitment to organizational objectives. The findings contribute to contemporary performance management literature by emphasizing the importance of employee-centered appraisal systems that integrate objective performance measurement with continuous feedback and career development opportunities. Practically, the study provides insights for organizations seeking to develop more adaptive and sustainable performance management practices for Generation Z employees.